TINGKAT KECEMASAN PADA IBU MENJELANG MENOPAUSE - Sutiyah Heni; Enur Nurhayati Muchsin (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Changes in the psychological state of premenopausal psychological conditions are depression (anxiety) caused by a decrease in the hormone estrogen. The decrease in the hormone estrogen causes a decrease in neurotransmitters in the brain that affect mood so if these neurotransmitters are low, feelings of anxiety will arise. The purpose of this study was to determine the level of anxiety in mothers before menopause in Sumberagung Hamlet, Sumberagung Village, Rejotangan District, Tulungagung Regency. Descriptive research design. The population is 300 respondents and a sample of 30 respondents. Purposive Sampling Technique. Questionnaire research instrument. The study was conducted on 9-20 March 2022. The variable level of anxiety in mothers before menopause. Data analysis is processed by the percentage formula and interpreted quantitatively. The results of this study were obtained from 30 respondents showing half of the respondents had moderate anxiety levels 15 respondents (50%,) almost half of the respondents had mild anxiety levels 10 respondents (33%), a small proportion of respondents did not have moderate anxiety levels 3 respondents (10% ), and a small proportion of respondents have a severe level of anxiety 2 respondents (7%). Factors that affect the level of anxiety are; education, living together, having received information, marital status, and work. Premenopausal mothers are expected to be able to participate in counseling about menopause and take advantage of information from various health agencies to avoid excessive anxiety.